Current Trends and Perspectives of Pressure Wire-Based Coronary Artery Bypass Grafting - Yoshiyuki Takami; Atsuo Maekawa; Koji Yamana; Kiyotoshi Akita; Kentaro Amano; Wakana Niwa; Kazuki Matsuhashi; Yasushi Takagi (Journal of Cardiovascular Development and Disease)
Fractional flow reserve (FFR) has been well validated as a modality for evaluating myocardial ischemia, demonstrating the superiority of FFR-guided percutaneous coronary intervention (PCI) over conventional angiography-guided PCI. As a result, the strategy for coronary artery bypass grafting (CABG) is shifting toward FFR guidance. However, the advantage of FFR-guided CABG over angiography-guided CABG remains unclear. While FFR-guided CABG can help avoid unnecessary grafting in cases of moderate stenosis, it may also carry the risk of incomplete revascularization. The limited use of FFR due to the need for hyperemia has led to the development of non-hyperemic pressure ratios (NHPRs). NHPR pullback provides trans-stenotic pressure gradients, which may offer valuable insights for CABG strategies. Recently, computed tomographic coronary angiography (CTCA) has emerged as a non-invasive modality that provides accurate data on lesion length, diameter, minimum lumen area, percentage stenosis, and the volume and distribution of high-risk plaques. With the introduction of FFR-CT, CTCA is now highly anticipated to provide both functional evaluation (of myocardial ischemia) via FFR-CT and anatomical information through serial quantitative assessment. Beyond the diagnostic phase, CTCA, augmented by automatic artificial intelligence, holds great potential for guiding therapeutic interventions in the future.